Regulation of water bodies to urban thermal environment: Evidence from Wuhan, China - Xie, Qijiao; Ren, Lu; Yang, Chenzhe (Frontiers in Ecology and Evolution, 2023)
Exploring how water bodies work on the thermal environment in a real and complex urban context is of great significance to develop urban blue infrastructure (BI) system for climate adaption. Previous studies mainly focused on the water cool island (WCI) effect in the microenvironment, which cannot provide enough evidence for systematic application. This study explored the cooling effect of water bodies on the urban environment in Wuhan, China based on three scenarios in which water bodies was regarded as individual samples, water network system and one landscape category of urban ecosystem respectively. Results indicate that all detected water bodies expressed WCI effect with the mean WCI intensity of 5.5℃ and the range of 1.1℃ to 13.3℃. The main factors influencing the cooling effect of urban water body system were Percent of landscape (PLAND_W), Landscape shape index (LSI_W) and Contrast-weighted edge density (CWED_W) of water bodies, which could explain 69.0% of urban LST variation. An urban water body system with relatively larger water area, more regular boundary and simpler surroundings might be more efficient in cooling the urban environment. Nevertheless, when considering the interaction of water bodies with other land covers on thermal environment, the contribution of water bodies to the cooling benefit was depressed. The main factors were Similarity index_mean of Construction land (SIMI_MN_C), Class area of Construction land (CA_C), Total edge contrast index of Water body (TECI_W), Landscape shape index of Water body (LSI_W) and Percent of landscape of Vegetated area (PLAND_V). They combined to explain 71.9% of LST variation in urban areas. Developing an urban BI system by connecting the dispersed water bodies and fragmenting the contiguous construction land in rapidly urbanized areas can be more realistic for mitigating UHI effect and adapting to climate change.